Digital Orthophoto Production Using Close-Range Photographs for High Curved Objects (Journal of Engineering, 2015)
Orthophoto provides a significant alternative capability for the presentation of architectural or archaeological applications. Although orthophoto production from airphotography of high or lower altitudes is considered to be typical, the close range applications for the large-scale survey of statue or art masterpiece or any kind of monuments still contain a lot of interesting issues to be investigated.In this paper a test was carried out for the production of large scale orthophoto of highly curved surface, using a statue constructed of some kind of stones. In this test we use stereo photographs to produce the orthophoto in stead of single photo and DTM, by applying the DLT mathematical relationship as base formula in differential rectification process. The possibilities and the restrictions of the used programs for the extraction of digital surface model & orthophoto production were investigated. The accuracy of the adjusted images using the digital differential rectification package, are checked using 3 check points and the RMSE was computed in 3-dimensions. Conclusions for usefulness and reliability of this test for such special applications were derived.